KIMYO FANINI O‘QITISH JARAYONINI TAKOMILLASHTIRISHDA MATEMATIKA FANI BILAN BOG‘LIQLIK ASOSIDAGI TOPSHIRIQLARDAN FOYDALANISHNING AHAMIYATI - Xasanova, X. (SCIENCE and SOCIETY, 2024)
In this article, the theoretical and practical significance of increasing students’ interest is presented in science through teaching with the help of creative tasks based on the integration of chemistry and mathematics. The importance of basing the subject on the connection of the subject with the subject of mathematics has been confirmed in increasing the effectiveness of teaching chemistry.